Unveiling the Impact of Emotional Regulation on Academic Procrastination - Ilmi, Rosa Devi Fitrotin; Ubaidillah, Hasan; Indayani, Lilik (Indonesian Journal of Islamic Studies, 2023)
This study examines how consumer perceptions of the Skintific brand, product quality, and pricing influence product selections among 110 FBHIS students at Muhammadiyah University of Sidoarjo. Using online questionnaires and quantitative analysis methods, including validity and reliability tests, multiple linear regression, and t-tests, the research reveals significant relationships between brand image, product quality, pricing, and consumer purchasing decisions. The findings emphasize the importance of these factors in shaping consumer behavior, particularly among university students, and offer insights for skincare companies targeting this demographic to enhance brand image, maintain product quality, and offer competitive pricing strategies. Highlight: Quantitative Analysis: Validity, reliability tests, regression for consumer behavior research. University Sample: Investigated FBHIS students' purchasing choices at Sidoarjo University. Strong Associations: Brand image, product quality, pricing linked to consumer decisions. Keywoard: Consumer perceptions, Skintific brand, Product quality, Pricing, Decisions